Analysis of Main Actors’Beauty Image in Korean TV Drama “Dokebi” - Yun, Un-Jae (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The beauty image studies in Korean TV dramas have been conducted around actresses.While this study aims to provide the basic data for the production of dramas, analyzing two main actors, Gong Yoo and Lee Dong-wook in “Dokebi,” which has been a fever in the U.S. and Europe as well as Asian countries, such as Taiwan and Japan, of the Korean TV dramas in 2017. Methods/Statistical analysis: This study would understand the beauty images centering around the capture images of the main actors in the drama, “Dokebi,” focusing on clothes, hairstyles, and accessories. In addition, this study would analyze somatotypes and face shapes, using an indirect measurement method and conduct a comparative study of somatotypes with Korean body measurements provided by the National Institute of Technology. Andit also conduct forface shapes with a 30-year-old man’s face shapes on culturecontent.com operated by the Korea Creative Content Agency. For personal colors, this study would analyze two actors’ skin colors, based on a third party, using Pantone’s Formula Guide and DIC Color Guide and look for colors complement them, using Adobe Photoshop CS5. Findings: It was found that Gong Yoo and Lee Dong-wook were taller and weighed less as compared to the standard somatotype, and as a result of a measurement of the ratio of their bodies with the head height, Gong Yoo was about 8.1 head figure, and Lee Dong-wook, about 7.5 head figure. For face shape, Gong Yoo’s face was smaller than Lee Dong-wook’s, and Gong Yoo’s face shape was an inverted triangle while Lee Dong-wook’s was a rectangle. For the beauty image, the number of clothes differed depending on the importance in the synopsis, and especially, since Gong Yoo symbolized a god of wealth, he put on expensive clothes of famous brands. Hairstyle did not change less than clothes, and the synopsis affected accessories the most. Through this study, it was found that somatotype or face shape had bigger impacts on the determination of the beauty image, rather than skin color, and also, for the color guides, an Asian, that is, Japanese color guide was applied better in finding Korean’s personal color rather than American products. Improvements/Applications: Studies of the beauty image have been conducted around women and people in their 20s, and celebrities’ the beauty images have also been investigated around actresses or idol groups. Thus, it is judged that this study has a value as a study of the beauty images of actors in their 30s. In addition, hopefully, this study will become the basic data for the production of dramas and a content material that promote Korea to the world.